INOVASI MODEL PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN KETERAMPILAN MENULIS BAHASA ARAB - Yesha Eka Yuana Putri; Aufia Aisa; Rina Dian Rahmawati (Jurnal Manajemen Pendidikan, 2026)
This study specifically aims to provide solutions to problems in learning Arabic, especially in writing skills. This study focuses on the implementation of the learning model project based learning (PjBL) in Arabic language learning. This study was applied using one-group pre-test post-test design, which compares the learning outcomes of students before and after treatment without a control group. The method used is a quasi-experiment using quantitative and qualitative approaches. The results showed a change in the paradigm of learning, which initially focused on the Learning Center educator (teacher-centered) switch to learners (student-centered). This study succeeded in increasing the involvement of students, and showed an increase in students ' writing skills. This is evident in the results of the analysis of pre-test and post-test scores using the wilcoxon test with a significance value (Z= -4.871; P <0.01) which shows that Ha is accepted and shows the significance of learners ' scores. This study has a novelty that specifically measures the improvement of writing skills through a real product in the form of Arabic concept maps, in contrast to previous studies that focused on learning interests. So that this study is able to provide practical implications for educators, namely analyzing and adopting the results of this study as a consideration and guidance in implementing a learning model.